The house that i live in the house that lives in me (DAPesquisa, 2020)
This text refers to the work developed with young children in an early preschool education institution. The daily work with children is inspired by movements that make up Playful/Artistic Inventions. In the combination of elements arising from relational psychomotricity, mainly from the perspective of French authors, Bernard Aucouturier and Andre Lapierre, and others from art, such as artists such as Lygia Clark, Elisa Bracher, Hélio Oiticica, Amélia Toledo, Deborah Colker, Leandro Selister, the Playful/Artistic Inventions sprout. The work is thought and planned, allowing children the opportunity to play with art, with artists, with works, propositions, materials and techniques. Spaces and times for playing are those in which children create.One of the aims of Playful/Artistic Inventions is to allow the child's body to arise, prioritizing a space-time in school routines for body-artistic work. The body-art instigating the child's desire to try out and to know, a space-time for the manifestation of what a child's body can. At the beginning of 2017, a pair of teachers defined A CASA as an allusion to work with children during that year. A CASA was, therefore, the element that nourished poetry and thought about the things of the world. Contemporary art in dialogue with performatic language, theater, cinema, dance and literature provided support for reflection on body and childhood in the school space.
Keywords: Performing arts and children; Body language in art; Play in art; Performance art